EVEROLIMUS IN DE NOVO RENAL TRANSPLANT RECIPIENTS - E. I. Prokopenko (Вестник трансплантологии и искусственных органов)
Survival of renal transplants and renal transplants recipients has improved greatly last years, but long-term graft survival remains unchanged. Nephrotoxicity of calcineurin inhibitors is one of the main factors of late renal allograft disfunction. Everolimus, new proliferation signal inhibitor, can facilitate minimization cyclosporine A exposure and has antineoplastic activity. The paper reviews literature dates regarding to clinical aspects of everolimus use in de novo renal transplant recipients.